2006
DOI: 10.1111/j.1478-3231.2006.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human immunodeficiency virus infection in patients infected with the hepatitis C virus

Abstract: In the present series there was no relevant impact of HCV infection in patients with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
2
13
1
3
Order By: Relevance
“…On the other hand, other authors have demonstrated that the progression of liver disease in HIV/HCV coinfected patients occurs primarily when the HIV infection is inadequately managed [12,13]. Confirming this hypothesis, Tovo et al assessed 385 HIV/HCV coinfected patients, and observed a similar fibrosis progression rate to that of HCV or HIV monoinfected patients [14].…”
Section: Introductionsupporting
confidence: 56%
“…On the other hand, other authors have demonstrated that the progression of liver disease in HIV/HCV coinfected patients occurs primarily when the HIV infection is inadequately managed [12,13]. Confirming this hypothesis, Tovo et al assessed 385 HIV/HCV coinfected patients, and observed a similar fibrosis progression rate to that of HCV or HIV monoinfected patients [14].…”
Section: Introductionsupporting
confidence: 56%
“…On the other hand, HAART may enhance liver damage in some HIV-HCV coinfected individuals through drug-related hepatotoxicity. Only 6 studies [28,32,35,38,39,42] in our analysis introduced the state of HAART in patients with HIV-HCV co-infection. The proportion of patients who were receiving HAART in cohort ranged 83%-95%.…”
Section: Discussionmentioning
confidence: 99%
“…Of them, 6242 were positive for HIV and 10508 were negative for HIV. Fourteen studies assessed the histological cirrhosis [9,18,19,21,[27][28][29][30][31][32]38,39,41,42] , 7 studies assessed the death [17,22,23,[34][35][36]40] , 3 studies assessed the decompensated liver disease [15,26,37] , 2 studies assessed the outcome of decompensated liver disease and death [16][17][18][19][20][21][22][23][24][25] , 1 study assessed the outcome of histological cirrhosis, hepatocellular carcinoma and death [20] , 1 study assessed the outcome of histological cirrhosis and death [24] , and 1 study assessed the outcome of hepatocellular carcinoma and death [33] , respectively. Most studies did not provide a racial distribution.…”
Section: Deng Lp Et Al Impact Of Hiv Infection On Hcv Infectionmentioning
confidence: 99%
“…The increase in patient survival numbers following the introduction of highly active antiretroviral therapy (HAART) has seen the emergence of HCV infection and chronic hepatic diseases as important morbidity and mortality causes together with HIV [2,3]. Similar transmission routes for HIV and HCV mean that coinfection is currently common, especially in injecting drug users and patients who have undergone blood transfusions, differing slightly from risk groups with isolated HIV or HCV [2,4,5]. It is estimated that 30% to 35% of HIV-infected patients in the United States of America are coinfected with HCV [2,6].…”
Section: Introductionmentioning
confidence: 99%